KESEHATAN KEUANGAN BANK TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN BANK BUMN DI BEI 2015-2019 - Dian Norma Pitasari; Imam Baehaki (Commodities, Journal of Economic and Business, 2020)
This research aims to analyze the financial health of banks on the profitability and corporate value of BUMN banks on the Indonesia Stock Exchange (IDX) during the period of 2015-2019. The population in this study was obtained using the Purposive sampling method and based on predetermined criteria, a sample of 4 BUMN bank companies was obtained. The analytical method used is multiple linear analysis with SPSS application tools. This variable is used in research, namely, Non Performing Loans (NPL), Loan to Deposit Ratio (LDR), BOPO and Capital Adequacy Ratio (CAR) as independent variables, and Return on Assets (ROA) and Price to Book Value (PBV) as variables dependent. The results showed that partially Capital Adequacy Ratio (CAR) had a significant effect on Return on Assets (ROA) and Price to Book Value (PBV) of bank BUMN listed on the IDX, Non Performing Loans (NPLs), Loans to Deposit Ratio ( LDR) has a significant influence on Price to Book Value (PBV) of listed state banks on the IDX while Non-Performing Loans (NPLs), Loans to Deposit Ratio (LDR) have an insignificant effect on ROA listed bank assets. on the IDX and BOPO have insignificant influence on the bank BUMN Price to Book Value (PBV) listed on the IDX and Return On Assets (ROA) have no significant effect on the bank BUMNPrice to Book Value (PBV) listed on the IDX. F test results state that the independent variables jointly affect the dependent variable under study.